The Comfort of Distance: Student Choices and Soft Skill Development during a Hybrid Hackathon in Post-Pandemic Learning - Gama, Kiev; Zimmerle, Carlos; Paganini, Lavinia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
The COVID-19 pandemic disrupted traditional educational methods, forcing a quick transition to emergency remote learning. With the subsequent rollout of COVID-19 vaccines, universities and society as a whole gradually resumed in-person activities. Students and university staff had to readjust to on-site learning and its associated challenges. This experience report specifically focuses on a course at University [omitted] dedicated to the design and development of Distributed Applications. Students engaged in a hybrid hackathon – an activity blending in-person and remote work – as part of the course. Despite their preferences for in-person collaboration, the majority of the students opted for remote participation. The goal of this report is to understand the students’ choices and adaptations to this new post-pandemic educational setting. We collected data through an anonymous survey and group interviews, revealing that the preference for remote work stemmed from convenience. Despite this, the distant collaboration allowed students to develop various soft skills. This exploration can shed light on future educational approaches in a world where online and in-person interactions can coexist.